Changes in number of granulosa cells during folliculogenesis in prepubertal goat ovary - SANGHA, G K; KHERA, K S; KAPIL, KANAN (The Indian Journal of Animal Sciences, 2011)
Histomorphological study in prepubertal goat ovary revealed the presence of primordial, intermediate, primary, secondary, and teritiary follicles. The primordial follicles were in abundance and occurred in series of 9 to 26 and even up to 40 follicles in a row. Initiation of follicle growth consisted of two distinct consecutive phases. The first phase was characterized by transformation of granulosa cells from a flattened to a cuboidal shape and by their proliferation. In the second phase an increase in the number of granulosa cells was accompanied by a rapid increase in the size of the oocyte. Oocyte commenced growth when there were at least 15 granulosa cells in the largest cross section. The oocyte diameter increased from 25.47 ± 1.14 Jllll (mean ± SE) in primordial follicles to 102.01 ± 2.15 Jlm in large antral follicles. The zona pellucida first appeared as small patches in primary follicles but formed a complete ring around the oocyte at the early antral stage. The average size of the secondary follicle was 138.07 ± 32.80 Jlm and teritiary follicle was 482.0 ± 148.67 Jllll. Large antral follicles may reach up to a diameter of 1537 flm in prepubertal goat ovary. It is concluded that some interrelationship exists between the number of granulosa cells around the follicle and the oocyte diameter1in all types of follicles.